2015
DOI: 10.1002/mop.29300
|View full text |Cite
|
Sign up to set email alerts
|

A note on material losses in unstructured transmission line modeling

Abstract: The incorporation of material losses within an unstructured transmission line Modeling electromagnetic field solver is presented. A theoretical and numerical development is complemented by a number of quantified canonical examples. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2218–2222, 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Particularly significant steps are highlighted as [30] and [34] as these have provided the robustness to scale and complexity demanded by installed antenna applications. Supporting evidence for the accuracy and multiscale capability of UTLM as well as its industrial deployment can be found in [27][28][29][30][31][32][33][34][35] which have primarily concerned EMC problems to date.…”
Section: The Utlm Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly significant steps are highlighted as [30] and [34] as these have provided the robustness to scale and complexity demanded by installed antenna applications. Supporting evidence for the accuracy and multiscale capability of UTLM as well as its industrial deployment can be found in [27][28][29][30][31][32][33][34][35] which have primarily concerned EMC problems to date.…”
Section: The Utlm Methodsmentioning
confidence: 99%
“…To undertake this study we apply, for the first time, the Transmission Line Modeling method using unstructured meshes (UTLM) [27][28][29][30][31][32][33][34][35] to the problem of installed antennas. Selection of this method proceeds from the well-known fact that unstructured meshes require notably fewer sample points to capture curved and multiscale geometries and if used intelligently in a hybrid fashion with Cartesian grids to model large empty space regions, this can be achieved without unduly compromising computational efficiency or with the complexity of bespoke sub-gridding techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an important advancement in the development of the UTLM method is its ability to deal with multiscale features of practical problems by deploying complexity reduction techniques in which small computational cells are coalesced into larger entities to reduce both pre-processing time and run time [27]. The UTLM method is not discussed in detail in this paper and supporting evidence for the accuracy and multiscale capability of the method, as well as its industrial deployment can be found in [19,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 97%
“…Being a time-domain method, the UTLM easily permits modeling of both linear, dispersive and nonlinear materials. Recent work has accounted for both electric and magnetic material losses [25], and the presence of carbon fiber panels as embedded thin film layers between the mesh cells [26]. Finally, an important advancement in the development of the UTLM method is its ability to deal with multiscale features of practical problems by deploying complexity reduction techniques in which small computational cells are coalesced into larger entities to reduce both pre-processing time and run time [27].…”
Section: Introductionmentioning
confidence: 99%